2021
DOI: 10.1093/tas/txab201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementing lactation and nursery pig diets with capsaicin on growth performance and gene expression of nursery pigs

Abstract: The objective of this study was to determine the effects of supplementing capsaicin in diets for lactating sows and their offspring on the growth performance and gene expression of pigs post-weaning. Twenty-eight multiparous sows were fed corn-soybean meal-based diets without (n = 14) and with (n = 14) capsaicin (2.5 mg/kg) during a 19-d lactation period. Litters from these sows (n = 288 pigs) were weaned and assigned to 36 blocks (pens) based on maternal dietary treatment and initial body weight (BW) to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The positive effect of CAP during this period may be due to higher feed utilization compared to the finisher period, because Sobolewska and Grela [20] found that the FCR of grower period was better than that of the finisher period. Accordingly, Rosa-Medina [7] found that dietary CAP increases the levels of digestive enzymes (amylase, protease and lipase) and digestibility of feed. Moreover, CAP reduces the demand of energy for maintenance because CAP activates the transient receptor potential vanilloid 1 (TRPV1) receptor in the nervous system and reduces metabolic stress [21].…”
Section: Growth Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The positive effect of CAP during this period may be due to higher feed utilization compared to the finisher period, because Sobolewska and Grela [20] found that the FCR of grower period was better than that of the finisher period. Accordingly, Rosa-Medina [7] found that dietary CAP increases the levels of digestive enzymes (amylase, protease and lipase) and digestibility of feed. Moreover, CAP reduces the demand of energy for maintenance because CAP activates the transient receptor potential vanilloid 1 (TRPV1) receptor in the nervous system and reduces metabolic stress [21].…”
Section: Growth Performancementioning
confidence: 99%
“…The CAP (trans-8-methyl-N-vanillyl-6-nonenamide) is a compound of lipophilic alkaloid [4], and up to 80% is passively absorbed in the segments of the stomach and the duodenum [5]. Several authors reported that the addition of CAP to pig diets significantly improved the small intestinal morphology of piglets [6] and increased the secretion of digestive enzymes through neurostimulatory activity [7]. According to other studies, CAP binds to heatsensing receptors and potentially reduces heat stress by manipulating cellular metabolism [1,7], providing antioxidant activity [8], and improving passive immunity [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation